Fear Of Missing Out Dalam Membentuk Self Control Dan Impulse Buying Pembelian Coffee Shop Viral Di Pontianak - Tantri; Octaviani, Dina; Arweni (Prodi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Panca Bhakti, 2025)
Coffee Shops in Pontianak are proof that people's interest in coffee is increasing. With unique concepts, diverse flavors, and a comfortable atmosphere, coffee shops in Pontianak have successfully captured the hearts of coffee lovers. This study aims to determine the influence of fear of missing out (FOMO) on self-control and impulse buying in viral coffee shops. The population in this study were people who had previously purchased coffee shops in Pontianak, selected using a purposive sampling method, resulting in a total sample of 100 people. This quantitative study tested hypotheses using SmartPLS3. The results showed that FOMO had a positive effect on purchases of viral coffee shops in Pontianak, self-control had a positive effect on purchases of viral coffee shops in Pontianak, and impulse buying had a positive effect on purchases of viral coffee shops in Pontianak